1983
DOI: 10.1901/jaba.1983.16-297
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Sign Language by Autistic Children Ii: Spontaneity and Generalization Effects

Abstract: Autistic children typically do not use their language repertoire in order to communicate.Six autistic children who exhibited poor communication skills were trained to use their sign repertoire to make spontaneous requests of adults. Training consisted of imitative prompting, fading, and differential reinforcement, and included aspects of incidental teaching. The children displayed an increase in the rate and variety of spontaneous sign requests (Experiment 1). Generalization of spontaneity across adults (Exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
100
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(101 citation statements)
references
References 35 publications
1
100
0
Order By: Relevance
“…For example, withholding reinforcement for appropriate be-havior that occurs at a low amplitude (e.g., speech loudness) could induce instances of higher amplitude behavior, which then could be maintained through reinforcement. Several studies have examined the use of extinction to increase behavioral variability (e.g., Carr & Kologinsky, 1983;Duker & van Lent, 1991;Lalli, Zanolli, & Wohn, 1994). For example, Duker and van Lent increased the number of different gesture requests exhibited by 6 individuals with developmental disabilities by withholding reinforcement for high-rate requests.…”
Section: Applied Research and Implicationsmentioning
confidence: 99%
“…For example, withholding reinforcement for appropriate be-havior that occurs at a low amplitude (e.g., speech loudness) could induce instances of higher amplitude behavior, which then could be maintained through reinforcement. Several studies have examined the use of extinction to increase behavioral variability (e.g., Carr & Kologinsky, 1983;Duker & van Lent, 1991;Lalli, Zanolli, & Wohn, 1994). For example, Duker and van Lent increased the number of different gesture requests exhibited by 6 individuals with developmental disabilities by withholding reinforcement for high-rate requests.…”
Section: Applied Research and Implicationsmentioning
confidence: 99%
“…One current approach to teaching language, pragmatics (Bates, 1976), minimizes the importance of training syntactic forms and emphasizes the training of communication skills that have functional effects on other people (Sailor et al, 1980). Under this approach, conversational skills such as greetings, expressing gratitude, turn-taking, topic maintenance, question asking, responding to questions, requesting objects or attention, and commenting on features of the setting or an event have been targeted for intervention (e.g., Carr & Kologinsky, 1983;Lancioni, 1982;Leifer & Lewis, 1984;Peck, Tomlinson, Schuler, Theimer, & Haring, 1984;Reichle, Rogers & Barrett, 1984;Warren, Baxter, Anderson, Marshall, & Baer, 1981).…”
mentioning
confidence: 99%
“…Gardner & Gardner (1969) began training an infant female chimpanzee, named Washoe, to use ASL (American Sign Language) as linguistic communication tool. Some researchers teach sign languages to autistic children who have failed to develop speech and who exhibited poor communication skills and found that sign languages are useful training way for them (Fulwiler & Fouts, 1976;Carr, Binkoff, Kologinsky, & Eddy, 1978;Carr & Kologinsky, 1983). Acredolo & Goodwyn (1985) taught normal infant symbolic gestures and found that despite the heavy use of symbolic gestures, vocal development was advanced.…”
Section: )mentioning
confidence: 99%